THE INFLUENCE OF ARTIFICIAL INTELLIGENCE UTILIZATION AND DIGITAL LITERACY ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE AT PT SEMEN INDONESIA LOGISTIK GROUP - Sudarman; Sutrisno, Timotius FCW; Andrina, Anak Agung Ayu Puty (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study examines the influence of artificial intelligence (AI) utilization and digital literacy on employee performance at PT Semen Indonesia Logistik Group, with work motivation as a mediating variable. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (SEM-PLS), data were gathered from 188 policy-making employees through an online survey. The results show that digital literacy significantly enhances both work motivation and employee performance, while AI does not have a direct or indirect significant effect. Work motivation plays a crucial mediating role, particularly in linking digital literacy to performance. The findings suggest that improving digital literacy is more impactful for boosting employee performance than AI implementation, which remains underdeveloped in this context. The study highlights the importance of a human-centered approach when integrating AI, as its improper use may reduce motivation and limit performance outcomes.